Integrin alpha5beta1 and resistance to cancer therapies: role of endocytosis in resistance to gefitinib - Silva, Elisabete Cruz da (2017)
Glioblastoma is an aggressive, invasive and resistant brain cancer. Despite the promisor role of EGFR, targeted therapies failed without giving insights about predictive factors. EGFR endocytosis and trafficking have been reported to influenciate therapy resistance. Integrin is known as a regulator of EGFR oncogenic activity during tumor progression by affecting its trafficking. Previous results from the team in cell evasion showed that α5 integrin depletion sensitizes cells to gefitinib treatment. For that, my main objective was to determine if the endocytic pathway is involved in the integrin-mediated resistance to gefitinib. Endocytosis involvement on gefitinib treatment was evaluated by dynamin inhibition. Dynamin is GTPase involved in the fission of endocytic vesicles. There were performed cellular evasion and EGFR internalization assays under gefitinib treatment with or without dynamin chemical inhibitiors (dynasore and dyngo4a). We showed that endocytosis is involved in the gefitinib-mediated inhibition of U87 cell evasion regardless the α5 integrin expression level. Gefitinib induces ligand-bound EGFR internalization, being this impaired with the addiction of dynasore. EGFR and α5β1 integrin distribution were evaluated using immunofluorescence confocal microscopy. Gefitinib was shown to induce internalization of both receptors, being them founded co-localized inside of early endosomal vesicles. Gefitinib induced EGFR internalization occurs in U87 and others glioma cell lines independently of α5 level. We postulate that α5β1 integrin may impact on EGFR trafficking and function during membrane trafficking after endocytosis confering resistance towards gefitinib treatment. There was already described a regulatory role of integrin in EGFR trafficking to promote carcinoma cell invasion, for that this role of integrin should be further evaluated. In conclusion, endocytosis plays a relevant role in gefitinib treatment. EGFR trafficking gains here a strong evidence for its role in therapy resistance. Modulators of this endosomal trafficking, such as α5β1 integrin can predict responsiviness towards EGFR targeted therapies.